Was Culture a Commodity ‘all’ Victorians Could Afford? – Notes on the First British Public Museums - Cláudia Martins (Anglo Saxonica, 2021)
The etymology of 'mouseion' gave rise to the word ‘museum’ and initially referred to the temple of the Muses. It is noteworthy to recall that the first museum was the Alexandria Museum, set up by Ptolemy in 300 B.C., as a temple, a library, an astronomical observatory, an amphitheatre, a botanical garden and a research venue (Anico 105). The outset of museums can be found later on in private collections, which continued until mid-18th century. Additionally, with the Enlightenment and the French Revolution, museums started being regarded as an ally to combat myths, dogmata and superstitions and thus ‘Curiosity Cabinets’ were gradually replaced by the first public museums, such as the Galleria degli Uffizi (1571), in Florence, the British Museum (1753), in London, and the Louvre Museum (1793), in Paris. Simpson (126–127) considers these new cultural spaces as a means for European powers to re-write their history and exhibit their past deeds, as well as a way to show off the heritage they unlawfully gathered in their colonial periods, in line with the 1851 Great Exhibition of the Works of Industry of all Nations, in London. Taking these assumptions into account, we aim at describing the birth of the first British public museums and the resources they wished to make available to their visitors (e.g. admission fees, facilities, lighting and guides), so as to reflect on the underlying concept of access to culture in Victorian mindset. Was culture a commodity then? In line with Kelly ('Culture as Commodity'), cultural products and services may have symbolic or even status-symbolic dimensions and this understanding leads us to a further question related to the target audiences of Victorian museums: Were they supposed to be accessible to everyone? Or were they merely for “the initiated” vs. “the primitive” (Chu)?